(untitled) (Culturas Científicas, 2026)
Should we consider the history and philosophy of physics as basic pillars for teaching and understanding science, or are they simply "lateral" knowledge that is dispensable for teachers? Can physics be taught without knowing its history and without resorting to epistemology? Let’s briefly reflect on the "traditional" way of teaching science: content is generally taught as finished products, not as the result of a process. Understanding what science is and how it is constructed, requires analyzing some historical cases of how theories were developed. In this brief essay, we will consider why we consider the use of history and epistemology to be central in the science classroom.